Oxidative stress in postmenopausal women. - Barrio, César (2015)
Among the currently most studied factors that contribute to aging is the critical role of oxidative damage, mainly generated by the own mitochondrial dysfunction in senescence. Permanent aggression by free radicals produced endogenously, it is the main expression of mitochondrial disorders.